2012
DOI: 10.4319/lo.2012.57.1.0281
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of changes in food quality and temperature reveals maternal effects on fitness parameters of a keystone aquatic herbivore

Abstract: We investigated the interaction of intergenerational temperature and food quality change on the fitness of two species of Daphnia, a freshwater keystone herbivore. The effect of a change in temperature (15uC vs. 20uC) and food quality (Cryptomonas sp. as high-quality food vs. Chlamydomonas sp. as relatively low-quality food) on juvenile growth rate and clutch size of Daphnia magna and Daphnia pulex was measured in 16 combinations of maternal and offspring environments in standardized growth assays. Both specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 56 publications
(112 reference statements)
1
23
0
Order By: Relevance
“…However, despite a higher content of single fatty acids, overall fatty acid content and the content of all major fatty acid types (saturated, monounsaturated, and polyunsaturated) were by trend reduced (by 10-25%; Supplemental Data, Table S3) in the fungicide treatment. This observation further supports the anticipated lower food quality of fungicide-exposed leaf material relative to control leaf material because diet quality for crustaceans is known to be highly dependent on the resources' fatty acid composition [45,46]. Furthermore, the applied fungicides also tend to adsorb to leaf material [8,12], suggesting their uptake via food.…”
Section: Effects On Gammarus Populationssupporting
confidence: 66%
“…However, despite a higher content of single fatty acids, overall fatty acid content and the content of all major fatty acid types (saturated, monounsaturated, and polyunsaturated) were by trend reduced (by 10-25%; Supplemental Data, Table S3) in the fungicide treatment. This observation further supports the anticipated lower food quality of fungicide-exposed leaf material relative to control leaf material because diet quality for crustaceans is known to be highly dependent on the resources' fatty acid composition [45,46]. Furthermore, the applied fungicides also tend to adsorb to leaf material [8,12], suggesting their uptake via food.…”
Section: Effects On Gammarus Populationssupporting
confidence: 66%
“…The saturation threshold approach used in our study to access possible interspecific differences between D. pulex and D. magna did not reveal significant results. We assume that the effect sizes depending on EPA-and ARA-supplementation were too similar to reveal any differences and therefore we suggest the experiments to be repeated at colder temperatures, where possible interspecific differences may be more visible due to a higher requirement for highly unsaturated fatty acids to maintain proper membrane fluidity (Hazel 1995;Valentine and Valentine 2004;Masclaux et al 2012;Pajk et al 2012). Nevertheless, we do provide evidence for interspecific differences in the response of the two Daphnia species that might be explained exclusively by insufficient amounts of EPA and/or ARA: the growth rate and the clutch size of D. magna along the EPA and ARA concentration clearly followed a saturation curve (between 30% and 50% of the variance was explained by the modified Monod model), while this was not the case for D. pulex.…”
Section: Interspecific Variationmentioning
confidence: 99%
“…However, there are few studies considering three or more variables simultaneously in the literature. One exception is Pajk et al (2012) who demonstrated that Daphnia fitness was affected not only by assay food quality and assay temperature, but also by maternal food quality and maternal temperature. These results suggest that simultaneously investigating multiple variables would provide more insights into understanding zooplankton responses to environmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to food quantity, interactions between temperature and food quality have recently come into focus. For example, the growth of D. magna did not respond to dietary phosphorus limitation when the temperature was the lowest, but was more depressed with increasing temperature (Persson et al 2011). Pajk et al (2012 reported that the interactions between temperature and food quality on the fitness parameters of D. magna and Daphnia pulex were influenced by maternal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation